An integrated valuation model for payer and investor - Mark Nuijten; Stefano Capri (Journal of Market Access & Health Policy, 2022)
Background In order to optimize positioning and associated drug price for both payer and investor, it is for a company essential to forecast the potential market access attractiveness for the new drug for different indications at the early onset of the clinical development program. This analysis must include the constraints from the perspective of the payer, but also the biotech companies, who require a minimum drug price to satisfy their investors. This paper aims to provide an Integrated Valuation Model for payer and investor, bridging concepts from health economics and economic valuation reflecting the perspectives of the payer and the investor for a drug in early clinical development phase. The concept is illustrated for a new hypothetical drug (Product X) in advanced breast cancer in 1-line, 2-line, and 3-line position.Methods The Integrated Valuation Model includes the outcomes of the budget impact model, pricing matrix model, and cost-effectiveness model reflecting the payer’s perspective. These models are interacted and linked with a discounted cash flow model in order to reflect also the economic value from the investor’s perspective.Results The maximum price in 1-line position is €269.7 for the payer and the minimum price is €14.7 for the investor, which are unit prices per administration corresponding with treatment regimens for the comparative treatments. In 2-line position, the maximum price is €274.1 for the payer and the minimum price for the investor increases to €184.5 for the investor because of the smaller market size in 2-line position, which leads to a smaller pricing corridor to satisfy both payer and investor. Consequently, Product X has market access attractiveness for both payer and investor in 1-line and 2-line position. However, the minimum price €942.7 in 3-line position for the investor is higher than the maximum price €283.3 for the payer, which means there is no market potential.Conclusion The practical strategic application of the Integrated Valuation Model is optimization of positioning and price of Product X. Hence, it can be a transparent tool in early-stage development of a compound based on upfront assessment of market access attractiveness for the payer and the investor.